Parental allele-specific protein expression in single cells In vivo. - Lo, C.A.; Chen, B.E. (Developmental Biology, 2019)
Allelic expression from each parent-of-origin is important as a backup and to ensure that enough protein products of a gene are produced. Thus far, it is not known how each cell throughout a tissue differs in parental allele expression at the level of protein synthesis. Here, we measure the expression of the Ribosomal protein L13a (Rpl13a) from both parental alleles simultaneously in single cells in the living animal. We use genome-edited Drosophila that have a quantitative reporter of protein synthesis inserted into the endogenous Rpl13a locus. We find that individual cells can have large (>10-fold) differences in protein expression between the two parental alleles. Cells can produce protein from only one allele oftentimes, and time-lapse imaging of protein production from each parental allele in each cell showed that the imbalance in expression from one parental allele over the other can invert over time. We also identify the histone methyltransferase EHMT to be involved in the protein synthesis dynamics within cells.